1999
DOI: 10.1046/j.1365-2567.1999.00732.x
|View full text |Cite
|
Sign up to set email alerts
|

Epitope mapping of 10 monoclonal antibodies against the pig analogue of human membrane cofactor protein (MCP)

Abstract: Pig membrane cofactor protein (MCP; CD46) is a 50 000-60 000 MW glycoprotein that is expressed on a wide variety of cells, including erythrocytes. Pig MCP has cofactor activity for factor I-mediated cleavage of C3b and is an efficient regulator of the classical and alternative pathway of human and pig complement. A panel of 10 monoclonal antibodies (mAbs) was collected from two different laboratories; all of these mAbs were raised against pig leucocytes and all recognized the same complex banding pattern on so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Immunohistology using a well‐characterized anti‐pig MCP monoclonal antibody 12 , 22 confirmed that MCP was abundantly distributed in pig tissues, particularly on cells of epithelial and endothelial origin (Fig. 4; Table 1).…”
Section: Discussionmentioning
confidence: 74%
“…Immunohistology using a well‐characterized anti‐pig MCP monoclonal antibody 12 , 22 confirmed that MCP was abundantly distributed in pig tissues, particularly on cells of epithelial and endothelial origin (Fig. 4; Table 1).…”
Section: Discussionmentioning
confidence: 74%
“…Clustering of the different mAbs based on a mAb-competition assay was previously shown for other proteins using a combination of biotinylated and non-biotinylated mAbs [44,45]. An excess of unbiotinylated mAbs was added to the cells and were allowed to bind to surface-expressed Sn for 60 min at 37 °C.…”
Section: Resultsmentioning
confidence: 99%
“… 20 Since expected results were obtained in the CHO system, similar expression trials were next carried out with two swine endothelial cell lines, SEC‐E and PAE. These cell lines expressed pig MCP, 19 which was detectable only with specific mAbs 19,30 Many clones expressing the four human MCP variants were successfully established ( Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…What works as an alternative receptor in SEC‐E cells is an intriguing issue. Although pigs have their own MCP on most tissue/organs, 19,30 , 32 the pig MCP does not act as a MV receptor (data not shown). It has been reported that ‘scatter‐like’ transdifferentiation was observed in endothelial and epithelial cells including hepatic cells treated with hepatocellular growth factor (HGF) 33,34 .…”
Section: Discussionmentioning
confidence: 96%